Game design : how to create video and tabletop games, start to finish - Pulsipher, Lewis, 1951- (Jefferson, NC : McFarland & Company, Inc., Publishers, 2012)
'The topics explored include the varying types of games, vital preliminaries of making a game, the nuts and bolts of devising a game, creating a prototype, testing, designing levels, technical aspects, and assessing nature of the audience. With practice challenges, a list of resources for further exploration, and a glossary of industry terms, this manual is essential'--Provided by publisher.
Includes index.
Keywords: Video games -- Design; Computer games -- Design